2019
DOI: 10.1177/1359104519895064
|View full text |Cite
|
Sign up to set email alerts
|

Managing risk and self-harm: Keeping young people safe

Abstract: Suicide is the second leading cause of death among adolescents worldwide, yet adequate mental health services for children and adolescents are lacking across the globe. Likewise, youth who engage in non-suicidal self-injury (NSSI) are at heightened risk for suicide, but few pediatric settings have established protocols for screening and responding to youth who engage in NSSI and/or endorse thoughts of suicide. In this article, we highlight similarities and differences of managing suicide and NSSI across cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 71 publications
(88 reference statements)
0
15
0
1
Order By: Relevance
“…31 The persistence of psychopathology among Group 1, furthermore, suggests that early screening measures if combined with prompt access to effective intervention could reduce the risk of future self-harm as well as improve mental health in the short term. 7 A second and highly tractable target for intervention is bullying, which casts a shadow over adult as well as childhood mental health. 32 This was a strong and early predictor of self-harm for children in the psychopathology pathway, preceding self-harm reports by 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The persistence of psychopathology among Group 1, furthermore, suggests that early screening measures if combined with prompt access to effective intervention could reduce the risk of future self-harm as well as improve mental health in the short term. 7 A second and highly tractable target for intervention is bullying, which casts a shadow over adult as well as childhood mental health. 32 This was a strong and early predictor of self-harm for children in the psychopathology pathway, preceding self-harm reports by 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its prevalence and lifelong consequences, there has been little progress in the accurate prediction of self-harm, 7 partly due to the unclear interaction(s) between the individual and external risk factors that predict it. 8 A study on adolescents in the UK found that repeated self- harm was strongly linked to personality disturbances, depression, substance use, troubled relationships with peers/family, poor school performance, and chronic psychosocial as well as behavioural problems.…”
Section: Introductionmentioning
confidence: 99%
“…Mental illness and suicide are highly stigmatized, which decreases the likelihood that some individuals will seek help (Corrigan et al, 2014). In some countries still today, suicide is considered illegal, and suicide attempts are punishable by time in prison rather than supported by time in mental health treatment and recovery (Westers & Plener, 2020). Moving away from criminalization of suicide behavior involves changing how we talk about it, such as ceasing use of the term “commit suicide” and replacing it with a more appropriate, non-criminalized description like “died by suicide.” We are also in the process of moving forward as a field by separating the person from the behavior.…”
mentioning
confidence: 99%
“…Moving away from criminalization of suicide behavior involves changing how we talk about it, such as ceasing use of the term “commit suicide” and replacing it with a more appropriate, non-criminalized description like “died by suicide.” We are also in the process of moving forward as a field by separating the person from the behavior. For instance, rather than call individuals “suicide attempters,” we may instead state, “an individual who attempted suicide.” Similarly, we are cautious to avoid using the terms “manipulative” or “gamey” when referencing suicide attempts, regardless of lethality, as these terms are inherently pejorative and stigmatizing (Westers & Plener, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation